PENDIDIKAN AGAMA: SEBUAH KEWAJIBAN RUMAH TANGGA PADA PERINGKAT AWAL - Muhammad AR (Jurnal Ilmiah Didaktika, 2012)
Children are Allah’s mandate entrusted to parents to be maintained, raise, educate and provide knowledge. The main task of parents is to educate and to provide religious knowledge, moral and other sciences which are useful for both one’s self and others. Parents are as the only most responsible person in determining an educational direction of the children. A good and bad moral is highly depending on early family educational process. If the parents are extremely concern and give extra attention to their children education, it certainly will produce a brilliant responsible man in his or her life.